Ecological risk assessment of heavy metals in the sediments and their impacts on bacterial community structure: A case study of Bamen Bay in China. (January 2023) - Li, Qipei; Pei, Lixin; Huang, Zanhui; Shu, Wei; Li, Qiuli; Song, Yanwei; Zhao, Hongwei; Schäfer, Marvin; Nordhaus, Inga
Abstract: Heavy metal pollution associated with human activity is of big concern in tropical bays. Microorganisms may be highly sensitive to heavy metals. Nonetheless, little is known about effects of heavy metals on microbial structure in tropical bay sediments. In this study, 16S rRNA gene sequencing and potential ecological risk index analysis were used to analyze the relationships between nine metals (arsenic, lead, cadmium, cobalt, chromium, copper, zinc, manganese, and nickel) and bacterial communities in the sediments of Bamen Bay, China. Our results showed that Bamen Bay was under a considerable ecological risk and cadmium had the highest monomial potential ecological risk. In addition, individual metal contamination correlated with bacterial community composition but not with bacterial α-diversity. Arsenic was the metal influencing bacterial community structure the most. Our findings provide a novel insight into the monitoring and remediation of heavy metal pollution in tropical bays. Graphical abstract: Unlabelled Image Highlights: Bamen Bay is under a considerable ecological risk. Cd had the highest monomial potential ecological risk based on RI. Proteobacteria was the dominant bacterial phylum. As was the heavy metal influencing bacterial community structure the most.